Scaling Behaviour of Si-alloyed Steel Slabs under Reheating Conditions - Mikl, Gregor; Höfler, Thomas; Gierl-Mayer, Christian; Danninger, Herbert; Linder, Bernhard; Angeli, Gerhard (Journal of Casting & Materials Engineering, 2021)
Reheating of steel slabs for further processing such as hot rolling usually takes place in gas-fired pusher furnaces. Temperatures well above 1000°C, combined with an atmosphere containing H2O, CO2, and O2, lead to substantial oxidation of most steel grades. Newly developed advanced steels often contain significant amounts of Si. This element plays a dominant role in the scaling behaviour near the steel-scale-interface, since fayalite (Fe2SiO4) forms a eutectic with wuestite (Fe1–xO) that melts as low as 1177°C.To better understand the high temperature oxidation behaviour, lab-scale trials were performed with different steel grades containing up to 3 wt.% Si. Possible interactions of Si with other alloying elements present in the samples such as Cr, Mn and Al were also of interest. The atmosphere contained 20% H2O, 7% CO2, and 3% O2, resembling reheating conditions in pusher furnaces, and temperatures ranged from 1100 to 1240°C. For metallographic investigation, the oxidised samples were cold mounted under vacuum using taper section angles. After preparation, the sections were examined through light microscopy, SEM/EDS, XRD, and TEM. The local distribution of the alloying elements could be mapped efficiently, and phase identification was successful in most parts. Under the applied experimental conditions, the elements of interest were present in their oxidic form either as pure or as mixed oxides. Higher Si-contents led to an increased build-up of eutectic melting phase at the steel-scale-interface at temperatures above 1177°C, which in turn further accelerated the oxidation.